PENGARUHPENGGUNAAN MEDIA PEMBELAJARAN MULTIMEDIA DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR BAHASA INGGRIS - Joesoef Anang; Fahri Yasin (Akademika, 2016)
This research aimed to figure out the influence of using intructional multimedia andinstructional printed media and the interactions between instructional media and learningdiscipline on English learning out comes. The research was conducted on Grade XI students ofSMAN 46 Jakarta is located at Jl. Mesjid Darussalam Kav 23- 25, Kebayoran Baru, JakartaSelatan. This research uses experimental methods with the dependent variable, treatmentvariable and attribute variable with design experiment factorial 2x2.The research has found through descriptive and inferential analysis that there were nodifferences on English learning outcomes among students were taught with multimediainstructional media and instructional printed media and there were no interaction betweeninstructional media and learning discipline. However, there were differences on learningEnglish outcomes between students were taught with instructional multimedia and instructionalprinted media that had a high or low learning discipline.